Preparation and planning of the hearing of the defendant for obtaining a lawful and complete testimony - Mirkov, Željko D. (Glasnik Advokatske komore Vojvodine, 2021)
The paper deals with the measures for the preparation and planning of the hearing of the defendant, taken by representatives of the police or prosecutor’s office. In the introduction, the author provides general observations on the hearing of the defendant and his testimony in the criminal procedure. The paper then proceeds to outline the views of theoreticians regarding the significance of the preparation and planning of the defendant’s hearing, as well as specific measures that need to be taken when carrying out this activity. These measures consist of the following: 1) determining the person who will conduct the hearing; 2) determining the location and time of the hearing; 3) analysis of the situation in the case files before the first hearing and identification of all facts and circumstances concerning the criminal offence; 4) obtaining information on the defendant’s personality, and 5) preparation of the hearing strategy. The author considers these measures necessary assumptions for obtaining not only a lawful testimony – in line with the provisions of the law on criminal procedure, but also a complete testimony, which is able to shed light on the facts surrounding the criminal offence.